2016
DOI: 10.1016/j.schres.2016.05.017
|View full text |Cite
|
Sign up to set email alerts
|

How much physical activity do people with schizophrenia engage in? A systematic review, comparative meta-analysis and meta-regression

Abstract: Our data confirm that people with schizophrenia engage in significantly less moderate and vigorous PA versus controls. Interventions aiming to increase PA, regardless of intensity are indicated for people with schizophrenia, while specifically increasing moderate-vigorous PA should be a priority given the established health benefits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
228
3
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 309 publications
(254 citation statements)
references
References 67 publications
14
228
3
9
Order By: Relevance
“…Of concern, a recent meta-analysis established that people with schizophrenia engaged in low levels of physical activity and approximately half do not meet the recommended weekly guidelines [10]. To date, a small number of studies [11,12] have suggested that lower levels of activity are associated with a worse metabolic profile.…”
Section: Introductionmentioning
confidence: 99%
“…Of concern, a recent meta-analysis established that people with schizophrenia engaged in low levels of physical activity and approximately half do not meet the recommended weekly guidelines [10]. To date, a small number of studies [11,12] have suggested that lower levels of activity are associated with a worse metabolic profile.…”
Section: Introductionmentioning
confidence: 99%
“…La proporción de pacientes activos es consistente con un reciente meta-análisis en pacientes con esquizofrenia (Stubbs et al, 2016), pero inconsistente con un estudio similar al nuestro (Vancampfort et al, 2016). Pese a que el resultado es superior al del estudio anteriormente mencionado (Vancampfort et al, 2016), la inactividad física sigue siendo un problema evidente en pacientes con esquizofrenia.…”
Section: Discussionunclassified
“…Los hallazgos de menor severidad de los síntomas psiquiátricos y mejor calidad de vida en pacientes activos concuerdan con estudios anteriores (Stubbs et al, 2016) y podrían ser debidos a los múltiples beneficios para la salud de la actividad física regular y ejercicio físico demostrados en pacientes con esquizofrenia (Vera-Garcia et al, 2015). Estos resultados refuerzan la necesidad de aumentar los niveles de actividad física en estos pacientes.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Notably, these illness outcomes are all elevated in schizophrenia. Persons with schizophrenia engage in less vigorous physical activity per day than healthy adults, but do engage in comparable levels of light physical activity, nearly 90 minutes per day (17). This may be due to the finding that walking is the primary means of transit for most persons with schizophrenia, and walking is a form of light exercise.…”
Section: Physical Activity and Exercise Interventionsmentioning
confidence: 99%